The Zamoyski Academy – History and Contemporary Times - Dyjakowska, Marzena; Kuryłowicz, Marek (Acta Universitatis Lodziensis. Folia Iuridica, 2023)
This article refers to Ireneusz Jakubowski’s research, tracing the historical fate of Roman law in Poland, as well as the commencement of activities of the New Zamoyski Academy in 2021. The authors refer to the slogans claiming that the Academy continues the tradition of the first Polish private university founded in the 16th century by Jan Zamoyski.